Microbiología de alimentos II : análise bacteriológica de leite - Joly, S. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1970)
This paper describes the results obtained from bacteriological analysis of 3 milk samples. It has been assumed that all milk samples have a high contamination level; for this reason the milk that is distributed to the people may be boiled prior to use, in order to protect the human health. The author claimes that anaerobic microorganisms have a important role in bacteriological water analysis and related ones. Thus it is quite clear that there is a ratio between the amounts of this bacteria groups. One such method would achiaved best results in bacteriological analysis.